1994
DOI: 10.1056/nejm199403313301304
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Acyclovir for 7 Days or 21 Days with and without Prednisolone for Treatment of Acute Herpes Zoster

Abstract: In acute herpes zoster, treatment with acyclovir for 21 days or the addition of prednisolone to acyclovir therapy confers only slight benefits over standard 7-day treatment with acyclovir. Neither additional treatment reduces the frequency of postherpetic neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(63 citation statements)
references
References 12 publications
1
58
0
4
Order By: Relevance
“…In this context, the absence of adverse effects from cortisone treatment of patients with PFP caused by borreliosis is important to note [7]. Steroids are also not contraindicated in the management of herpes zoster but may rather serve to reduce acute pain and to speed healing of the vesicles [43]. In the future, extensive virologic and immunologic studies should enable us to further reduce the frequency of a diagnosis of ‘idiopathic’ PFP and to unravel possible mechanisms for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the absence of adverse effects from cortisone treatment of patients with PFP caused by borreliosis is important to note [7]. Steroids are also not contraindicated in the management of herpes zoster but may rather serve to reduce acute pain and to speed healing of the vesicles [43]. In the future, extensive virologic and immunologic studies should enable us to further reduce the frequency of a diagnosis of ‘idiopathic’ PFP and to unravel possible mechanisms for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that acyclovir treatment speeds the healing of the rash to within 1-2 days and also relieves acute pain [8,14], but it does not prevent the occurrence of PHN [8,[15][16]. In addition, treatment with both acyclovir and corticosteroids has the same effect as treatment with acyclovir only [8,14,17]. Opioids and some antiepileptic drugs (e.g., gabapentin) are used to relieve acute pain, whereas tricyclic antidepressants are used for the prevention of PHN [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…50 years, have moderate to severe pain at presentation, and have no contraindications for its use. [49][50][51] Acute Hz-related pain can be controlled with the use of a short-acting narcotic analgesic agent (eg, oxycodone) given on a scheduled rather than on an as-needed basis, a 5% lidocaine patch, gabapentin or amitriptyline in addition to oral analgesic agents, oral prednisone in addition to an antiviral agent and an analgesic agent, an epidural injection of methylprednisolone acetate and bupivacaine (once or repetitive) in addition to an oral analgesic agent, ganglion blockade with bupivacaine and dexamethasone, and/or acupuncture. Topical capsaicin should not be used in patients with active Hz because it can exacerbate pain, but it can be used for the treatment of PHN.…”
Section: Treatmentmentioning
confidence: 99%